2010
DOI: 10.1158/0008-5472.can-09-4672
|View full text |Cite
|
Sign up to set email alerts
|

Different Tumor Microenvironments Contain Functionally Distinct Subsets of Macrophages Derived from Ly6C(high) Monocytes

Abstract: Tumor-associated macrophages (TAM) form a major component of the tumor stroma. However, important concepts such as TAM heterogeneity and the nature of the monocytic TAM precursors remain speculative. Here, we show for the first time that mouse mammary tumors contained functionally distinct subsets of TAMs and provide markers for their identification. Furthermore, in search of the TAM progenitors, we show that the tumor-monocyte pool almost exclusively consisted of Ly6C hi CX 3 CR1 low monocytes, which continuo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

59
1,065
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,058 publications
(1,131 citation statements)
references
References 49 publications
59
1,065
3
4
Order By: Relevance
“…IDO is also produced by MDSCs, regulatory dendritic cells and TAMs [6,52,125,126]. Silencing of IDO within the tumor using Salmonella typhimurium as a tumor-homing vector to deliver a short-hairpin RNA targeting IDO, allowed tumor infiltration of activated ROS-producing neutrophils and consequent tumor cell death [127].…”
Section: Other Immunosuppressive Moleculesmentioning
confidence: 99%
“…IDO is also produced by MDSCs, regulatory dendritic cells and TAMs [6,52,125,126]. Silencing of IDO within the tumor using Salmonella typhimurium as a tumor-homing vector to deliver a short-hairpin RNA targeting IDO, allowed tumor infiltration of activated ROS-producing neutrophils and consequent tumor cell death [127].…”
Section: Other Immunosuppressive Moleculesmentioning
confidence: 99%
“…1). In cancer, it is becoming clear that TAMs, like other members of the myeloid family, are incredible heterogeneous and depending on the tissue and type of tumor, the stage of tumor progression and location within the tumor tissue, different subpopulations of TAMs may differ considerably in terms of function and phenotype [27,56].…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%
“…A recent study, using multiple mouse tumor models, demonstrated that multiple subpopulations of TAMs (and/or potentially monocyte-derived transition stages) could be consistently identified based on their expression of surface markers such as Ly6C and MHC [56]. These sub-populations localized to different regions of the tumor microenvironment (such as hypoxic and normoxic regions) and had distinct functions.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations